(untitled) (Scientia Agropecuaria, 2016)
The aim of this study was to analyze the response of P. vulgaris to single inoculation or to PGPM of dose reduced to 50% of NF. In that sense seeds of P. vulgaris were inoculated individually with B. cereus, R. etli or T. harzianum and as a PGPM consortium in a hydroponic system Leonard jars, fed with NH4NO3 (ammonium nitrate) 50%, reduced dose. Under an experimental randomized block design; response variables measured were: percentage and days to germination, plant height and root length, weight fresh/ dry air and root weight (AFW/ADW/RFW/RDW) to seedling and flowering, experimental data were validated by Tukey, p ≤ 0.05. Results showed that P. vulgaris inoculated with R. etli and T. harzianum had 100% and 95.8% germination in 4.8 and 4.5 days respectively and statistically different compared to 91.7% in 7.17 days of P. vulgaris not inoculated at 100% NF had as a Fertilizer Control (FC). At seedling stage of P. vulgaris with T. harzianum and R. etli had 1.12 g and 0.72 g of ADW and of 0.31 and 0.21 g RDW; while P. vulgaris response used as FC with 0.52 g and ADW and 0.19 g of RDW. This supports the positive potential of R. etli and T. harzianum for producing P. vulgaris reduced dose of NF, as well the positive effect of B cereus and microbial consortium in the legume.